Maketa . Model House - Radovanovic, Goran (Serbia and Montenegro, 2001)
Soros Documentary Fund “Model House” is the story of a Serbian cleaning woman who is an ex-Yugoslav refugee from the Krajina region. Although she is grateful to be working, taking care of the homes of others reminds her of the home she lost during the war. Her narrative is juxtaposed with scenes from the NATO bombing, visuals of dingy refugee camps, excerpts from state television broadcasts spewing inane propaganda, and a voiceover of Milosevic intoning, among other things, "All must be sacrificed for the people, except the people."